The surface chemical bond of a nonbenzenoid aromatic hydrocarbon: Acepleiadylene versus pyrene - Ruppenthal, Lukas; Ruan, Zilin; Schramm, Jakob; Liu, Pengcai; Münster, Florian; Naumann, Tim; Neuhaus, Leonard; Herritsch, Jan; Chen, Xing Yu; Wang, Xiao Ye; Meyer, Bernd; Tonner-Zech, Ralf; et al. (Surface Science, 2025)
Defects play a critical role in the performance of carbon-based (opto-)electronic materials, because the materials’ interaction with metal electrodes can strongly depend on the topology of the π-electron system. However, the direct investigation of defects is difficult due to their typically low density. To address this issue, we use a molecular model system comparing the polycyclic aromatic hydrocarbon pyrene with its isomer acepleiadylene regarding their interaction with a Cu(111) surface. Acepleiadylene serves as a model defect with a nonbenzenoid nonalternant topology, while pyrene represents an ideal benzenoid alternant structure. We find that acepleiadylene forms a stronger bond to the metal surface than pyrene. This is evidenced by a higher molecule-surface bond energy, significant adsorption-induced changes in electronic structure (studied via photoelectron and X-ray absorption spectroscopies), and a potentially lower adsorption height (according to non-contact atomic force microscopy). The stronger bond of acepleiadylene is linked to its smaller gap between the highest occupied and the lowest unoccupied orbitals (HOMO-LUMO gap), bringing the LUMO closer to the metal's Fermi energy and resulting in stronger hybridization with the metal's electronic states. Density functional theory calculations support our findings, suggesting that nonbenzenoid, nonalternant structural elements can enhance the bonding between graphene-based materials and metal electrodes. Additionally, these results highlight the potential of nonbenzenoid molecular organic semiconductors as alternatives to their benzenoid counterparts.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Electronic structure; Graphene; Metal-organic interface; Nanographene; nc-AFM; Polycyclic aromatic hydrocarbon; XPS